Learning the Prophet Muhammad’s Da’wah History to Improve Students’ Spiritual Intelligence - Juliastuti, Juliastuti; Azijah, Silvi Nur; Haetami, Ahmad (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2023)
The study's overarching goal is to shed light on how educators might help their pupils grow spiritually by studying Islamic cultural history and the teachings of the Prophet Muhammad. The goal of this qualitative research is to provide a narrative description and explanation of the actions taken. Information gathered from class X (tenth grade) students' firsthand accounts of classroom instruction and classroom activities at Madrasah Aliyah Negeri 1 in Tangerang Regency. According to the findings, educators can improve their own spiritual intelligence by studying Islamic cultural history through the teachings of the Prophet Muhammad. By using the example method of instruction, we can learn about the qualities that the Prophet Muhammad possessed and taught, such as diligence, perseverance, accountability, patience, and unwavering commitment to spreading Islam. The next step is to incorporate bartering questions into student discussions as a means of encouraging them to be more receptive to new ideas and perspectives. This is because students work in groups to generate and respond to questions, as well as to explain and critique one another's answers. As a result of their involvement with the religion that the Prophet Muhammad battled for, pupils develop spiritual indicator intelligence, a strong feeling of caring, a tendency to be generous, and an enduring desire to be of service to others.